Struktur Anatomi Akar, Batang dan Daun Anthurium plowmanii Croat., Anthurium hookeri Kunth. dan Anthurium plowmanii Ã— Anthurium hookeri - Riza Linda, Nurhayati, Mukarlina, (Jurnal Protobiont, 2016)
The anthurium seedlings are not only supplied through vegetative propagation, but also through generative propagation, i.e. plant crossing that also functions to enhance the exotic values which are different from the parent anthurium. Crossing the parent anthurium not only produces new plants with a different morphology, but also affects the anatomy of the plant itself. This research aimed to find out the anatomical structure of the root, stem and leaves of A. plowmanii and A. hookeri as well as the hybrid of both plants. The research was carried out from January to September 2015. The preparations of the organ incision were made using aparaffin method. The structure of vascular bundles of the A. hookeri stem showed a significant difference compared to the other two types. In addition, the ergastic substance was found more in the hybrid plant compared to both of its parent plants.